2020
DOI: 10.1007/s11414-020-09714-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mental Health Treatment on Suicide Attempts

Abstract: This paper analyzes the impact of mental health treatment on suicide attempts. While prior work demonstrates the effectiveness of mental health treatment at reducing suicide risk, few studies examine nationally representative populations or use broad measures of access to mental health services. A methodological problem can arise in studies of mental health treatment and suicidal behavior because a suicide attempt can result in the use of more mental health services. Using nationally representative survey data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…During adolescence, higher use of mental health treatment utilization has been shown to associate with the risks of suicide behaviors (McClellan et al 2020 ). Most studies, however, were conducted using cross-sectional design (Nock et al 2013 ) or followed up over a short term (e.g., 6-month follow up; Moskos et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…During adolescence, higher use of mental health treatment utilization has been shown to associate with the risks of suicide behaviors (McClellan et al 2020 ). Most studies, however, were conducted using cross-sectional design (Nock et al 2013 ) or followed up over a short term (e.g., 6-month follow up; Moskos et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Estimates indicate that more than 90% of people who die by suicide had at least one mental disorder, with emphasis on the lack of access to treatment that highlights the omission of mental health care, an action with potential for preventing deaths by suicide. 19 The World Health Organization emphasizes depression and alcohol use disorders as the most incident disorders related to suicide. 1 However, it is worth noting that suicidal behavior is multifactorial, and is not the exclusive product of the prior existence of mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment may include inpatient or outpatient services in which various therapies and pharmaceutical approaches may be utilized. Research has shown that mental health treatment does, in fact, reduce the risk of suicide (Katz et al, 2013;McClellan et al, 2021). However, it has also evidenced that mental health treatment utilization is significantly lower in individuals with depressive symptoms and suicidal ideation (Deane et al, 2001;Hom et al, 2015).…”
Section: Mental Health Treatmentmentioning
confidence: 99%
“…Mental health treatment may work as a protective barrier for suicide and so understanding the accessibility and availability of various mental health services is important in suicide prevention (McClellan et al, 2021). Those individuals with the highest risk for suicide (i.e., those with suicidal ideation or a history of suicide attempts) are the most difficult to include in various mental health treatment centers and services, as this population is often prone to early program termination (McClellan et al, 2021). However, increases in outpatient service staffing, increased funding, widely implemented resources, and greater accessibility have the potential to alleviate the pressures of ineffective mental health treatment (Katz et al, 2013).…”
Section: Mental Health Treatmentmentioning
confidence: 99%
See 1 more Smart Citation